2011
DOI: 10.1111/j.1442-200x.2010.03295.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hypothermia in preterm infants with polyethylene wrap

Abstract: Wrapping premature infants with gestational age <34 weeks in polyethylene plastics immediately after birth is associated with lower incidence of hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 14 publications
0
46
0
14
Order By: Relevance
“…As shown in trials of preterm very low birth weight and low birth weight infants, 10,17,18 there was a positive correlation between birth weight and temperature at 1 hour after birth, but the correlation was weaker in the intervention group, suggesting that the plastic bag has a greater effect on infants with a lower birth weight. Even neonates who were normothermic at 15 minutes after birth benefited from the plastic bags by developing a lower rate of moderate hypothermia and smaller decreases in axillary temperature over the first hour after birth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in trials of preterm very low birth weight and low birth weight infants, 10,17,18 there was a positive correlation between birth weight and temperature at 1 hour after birth, but the correlation was weaker in the intervention group, suggesting that the plastic bag has a greater effect on infants with a lower birth weight. Even neonates who were normothermic at 15 minutes after birth benefited from the plastic bags by developing a lower rate of moderate hypothermia and smaller decreases in axillary temperature over the first hour after birth.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 Randomized trials of plastic bag use during the first hour after birth in larger preterm infants showed decreased rates of hypothermia. [17][18][19] It is possible that the addition of the plastic bag to standard WHO thermoregulation care may be an effective intervention to decrease rates of hypothermia in term neonates. The current trial sought to determine if placing term infants in polyethylene plastic bags at birth reduces hypothermia 1 hour after birth.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, evidence that suggests plastic wrap coverings reduce the risk of intraventricular hemorrhage is statistically insignificant [20,25,26]. Moreover, past findings reveal that plastic wraps do not completely decrease the risk of respiratory distress syndrome [20]. Further studies to investigate the impact of plastic wraps on neonatal morbidity and mortality are warranted.…”
Section: Polyethylene Occlusive Wrapmentioning
confidence: 99%
“…There are a large number of proofs or past incidents that swaddling preterm neonates with plastic bag immediately after birth reduces heat loss and is as effective as standard thermoregulation procedures [18][19][20]. Yet, it doesn't reduce heat loss in neonates aged 28 to 31 weeks [21].…”
Section: Polyethylene Occlusive Wrapmentioning
confidence: 99%
See 1 more Smart Citation